Integrated PIN modulator and photodetector operating in the mid-infrared range from 5.5 μm to 10 μm - Nguyen Thi Hao Nhi; Turpaud Victor; Koompai Natnicha; Peltier Jonathan; Calcaterra Stefano; Isella Giovanni; Coudevylle Jean-René; Alonso-Ramos Carlos; Vivien Laurent; Frigerio Jacopo; Marris-Morini Delphine (Nanophotonics)
This study reports the experimental demonstration of the first waveguide-integrated SiGe modulator using a PIN diode operating in a wide spectral range of the mid-infrared region. At the wavelength of 10 µm, an extinction ratio up to 10 dB is obtained in injection regime and 3.2 dB in depletion regime. High speed operation is obtained, up to 1.5 GHz. Furthermore, the device can also operate as an integrated photodetector. Photodetection has thus been characterized from 5.2 µm to 10 µm wavelengths showing an internal responsivity around 1 mA/W, and a 3 dB electro-optical bandwidth of 32 MHz. These results show a significant advancement in integrated photodetectors and electro-optical modulators for mid-infrared spectroscopy.